Kesiapan Belajar Siswa SMA N 1 Pinggir Kecamatan Pinggir Riau dalam Memilih Pendidikan Lanjutan - Hayati, Nurmala; Deswalantri, Deswalantri (Lembaga Yasin AlSys, 2024)
This research itself was motivated by the discovery that one of the students at SMAN 1 Pinggir, Pinggir Riau District was see n daydreaming, which after the author asked and followed up with the students and also the guidance and counseling teacher at the school, it turned out that the problem was regarding the student's learning readiness in determining further education. So this research aims to determine the learning readiness of students at SMA N 1 Pinggir, Pinggir Riau District in choosing further education. This research uses field research with a qualitative descriptive approach. The key informants were students of SMA N 1 Pinggir, Pinggir Bengkalis District, Riau and supporting informants, BK teachers, SMA N 1 Pinggir, Pinggir Bengkalis District, Riau. Data was collected through interviews and observations and analyzed by data reduction, data presentation, and data conclusions. The results of this research are that students have good readiness in choosing further education. Factors that influence students' learning readiness in terms of intelligence, interest, motivation, concentration of attention and also that students have good provisions and decisions regarding their further education, SMA N 1 Pinggir students have the choice in choosing further education. This is a form of learning readiness that has been they have. Schools and guidance and counseling teachers at scho ols provide motivation to students and hold seminars regarding the goals and functions of why they should continue to further education.